Hunter's disease in a girl: association with X:5 chromosomal translocation disrupting the Hunter gene. Issue 11 (November 1983) - Mossman, J; Blunt, S; Stephens, R; Jones, E E; Pembrey, M
Abstract : We describe a 3 year old girl with the typical clinical features of the X linked recessive condition, Hunter's disease. The diagnosis was confirmed by the pattern of urinary excretion of glycosaminoglycans and the absence of iduronate sulphatase activity in her fibroblasts. She also had an apparently balanced reciprocal chromosomal translocation 46XX, t(X:5) with the X breakpoint being between q26 and q27. Pedigree analysis, and the normal iduronate sulphatase activity in the mother's fibroblasts, serum, and hair roots indicate that the affected child represents a new mutation. Since the parents' karyotypes are normal, it seems that the translocation disrupted the iduronate sulphatase gene itself, thus mapping this to Xq26-27 for the first time. The severe clinical features, not expected in a girl, may be explained by non-random X inactivation.